2020
DOI: 10.1101/2020.04.27.063065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification and transcriptional analyses of MATE transporter genes in root tips of wildCicerspp. under aluminium stress

Abstract: 26Chickpea is an economically important legume crop with high nutritional value in human diets. 27 Aluminium-toxicity poses a significant challenge for the yield improvement of this increasingly 28 popular crop in acidic soils. The wild progenitors of chickpea may provide a more diverse gene pool 29 for Al-tolerance in chickpea breeding. However, the genetic basis of Al-tolerance in chickpea and its 30 wild relatives remains largely unknown. Here, we assessed the Al-tolerance of six selected wild 31 Cice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
0
1
Order By: Relevance
“…This is because the number of MATEs we identified for species differs from existing data in some instances, which we believe reflects likely differences in the use of genome assemblies/annotations, selection criteria, and data download sources. For example, our CarMATEs count ( n = 48) is relatively low compared to that reported by Zhang et al (2020) , who identified 56 CarMATEs using the reference genome of the CDC Frontier available in the NCBI database (BioProject: PRJNA190909 ). At the same time, compared with previous studies, we identified comparable numbers of MATEs in the dicot model Arabidopsis ( Arabidopsis thaliana ; n = 57) and the monocot model rice ( Oryza sativa ; n = 55; Huang et al, 2019 ; Qiao et al, 2020 ), which further validates our identification strategy based on the MATE-domain based hmm profile search.…”
Section: Discussioncontrasting
confidence: 62%
“…This is because the number of MATEs we identified for species differs from existing data in some instances, which we believe reflects likely differences in the use of genome assemblies/annotations, selection criteria, and data download sources. For example, our CarMATEs count ( n = 48) is relatively low compared to that reported by Zhang et al (2020) , who identified 56 CarMATEs using the reference genome of the CDC Frontier available in the NCBI database (BioProject: PRJNA190909 ). At the same time, compared with previous studies, we identified comparable numbers of MATEs in the dicot model Arabidopsis ( Arabidopsis thaliana ; n = 57) and the monocot model rice ( Oryza sativa ; n = 55; Huang et al, 2019 ; Qiao et al, 2020 ), which further validates our identification strategy based on the MATE-domain based hmm profile search.…”
Section: Discussioncontrasting
confidence: 62%